Computer aids to oilwell casing design and their economics - Lee, Yen-yu; Radok, Rainer; Vilas Wuwongse; Orth, Hermann M.; R.O.C. Government (Bangkok : Asian Institute of Technology, 1983)
This work computerizes the existing casing design system of the Drilling Department of the Taiwan Petroleum Exploration Division of the Chinese Petroleum Corporation. An analysis and identification of the functions and main problem areas of the existing system have been conducted in order to design the computerized system. The computerized casing design system comprises four modules: 1. DETERMINE SETTING DEPTH from three control factors: pressures, working days, and special points. 2. SELECT OPTIMAL CASINGS for a combination casing string, using a binary tree traverse method to find the cheapest combination from all possible combinations with the minimum memory space, and quickest in speed. 3. FORECAST ANNUAL CASING DEMAND, using distribution free and normal distribution methods to minimize the understock loss. 4. QUERY PROCESSING AND INFORMATION UPDATING, employing a binary search technique, inverted files, and other data structures. All files and programs needed to support the computerized system have been developed and tested.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Oil well casing -- Automation